Investigation on dry machining of stainless steel 316 using textured tungsten carbide tools - P M Mashinini; Hargovind Soni; Kapil Gupta (Materials Research Express, 2019)
In this research, austenitic stainless steel SS316 material has been machined using textured carbide cutting tools under dry conditions. Micro-textures were made on tool rake face using wire spark erosion machining technology. Effects of three important machining process parameters i.e. cutting speed, depth of cut and feed rate on machinability (MRR, average roughness, and tool wear) of SS316 have been investigated. Taguchi L _27 orthogonal array based twenty seven experiments have been carried out by varying machining parameters at three levels. Feed rate has been identified as the most important parameter. Machining parameters have been optimized by grey entropy method to enhance the machinability. Optimal combination of machining parameters i.e. 170 m min ^−1 cutting speed, 0.5 mm/rev feed rate and 1.5 mm depth of cut produced the best machinability with 3.436 μ m average roughness, 105187 mm ^3 min ^−1 . MRR, and tool wear 234.63 μ m. Lastly, a tool wear and chip morphology study have been done where textured tools have been found outperformed plain (Non-textured) tools.